Curcumin as a Potential Hypoglycaemic Agent for Managing Oxidative Stress - Debnath, Ashmita; Ali, M. A.; Deshmukh, Kaivalya; Das, Ajoy; Shantabi, Longjam; Elangbam, Shrilla (International Journal of Bio-resource and Stress Management, 2025)
This review outlined the basic mechanisms by which curcumin exerted protective effects in diabetes and discussed its potential as a supportive treatment for oxidative stress-related metabolic disorders. Curcumin, a yellow compound from the rhizomes of Curcuma longa, the primary active ingredient in turmeric. It was a lipophilic polyphenol, a bis-a, b-unsaturated b-diphenone, with the chemical formula C21H20O6 and the name (E,E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione. This plant had several biological properties like antimicrobial, anti-inflammatory etc and one of which included anti-diabetic property as well. Diabetes mellitus was a metabolic disorder that has reached pandemic proportions world-wide. As the incidence of type 2 diabetes mellitus (T2DM) continues to rise globally, oxidative stress and inflammation have emerged as major drivers of its progression and complications. Oxidative stress plays a crucial role as one of the major causes of diabetes, as it leads to the destruction of pancreatic beta cells and a consequent lack of insulin production. Therefore, curcumin contributed to redox balance by enhancing the activity of endogenous antioxidant systems through the Nrf2-ARE signalling pathway and limiting inflammatory responses via inhibition of NF-κB. Additionally, it supported glucose regulation by improving insulin sensitivity, promoting glucose uptake, and reducing hepatic glucose production. Despite these promising effects, curcumin’s therapeutic use was challenged by its poor oral bioavailability, leading to exploration of advanced delivery strategies including nanoparticles, liposomal encapsulation, and phytosome formulations.